Contextual analysis of the rural poor experience in relation to limitation of livelihoods information access - Yusup, Pawit M.; Subekti, Priyo; Rohanda, Rohanda (Faculdade de Filosofia e Ciências, 2016)
Studies on the rural poor are continuously performed using either the multidimensional or contextual approach. This study was conducted to analyze the meaning of poor from an emic approach, especially in the context of the specific aspect of limited access to livelihoods information. By using the qualitative method and phenomenological tradition of Schutz, the results showed that the rural poor had the following experiences: (1) were less fast in the skirmish to obtain livelihoods information; (2) no one ever told them concerning the existence of livelihoods information they desperately needed; (3) not much could be done to increase their income; (4) had no knowledge and experience of reading literature on entrepreneurial-based businesses; (5) felt no need to seek livelihoods information; (6) could not bear to see people fighting each other to obtain livelihoods information ; (7) was not able to seek and obtain livelihoods information; (8) were ignorant of the existence of books or literature regarding successful entrepreneurship; (9) had insufficient time for reading books and other reading materials on entrepreneurship; and (10) had limited experience in seeking and using livelihoods information.